TBC1D2 Promotes Ovarian Cancer Metastasis via Inducing E-Cadherin Degradation - Tian, Jiming; Liang, Xiaolei; Wang, Dalin; Tian, Jinglin; Liang, Haiping; Lei, Ting; Yan, Zeyu; Wu, Dan; Liu, Xiaoli; Liu, Shujuan; Yang, Yongxiu (Frontiers in Oncology, 2022)
Background Ovarian cancer (OC) is the most lethal gynecological malignancy worldwide. Increasing evidence indicates that TBC domain family is implicated in various cellular events contributing to initiation and development of different cancers, including OC. However, the role of TBC1D2, a crucial member of TBC domain family, remains unclear in OC. Methods IHC and qRT-PCR were employed to determine TBC1D2 expression in OC tissues and cells. In vitro and in vivo assays involving proliferation, migration, invasion were performed to explore the role of TBC1D2 in OC development. The underlying mechanism by which TBC1D2 promotes OC metastasis were elucidated using bioinformatics analysis, western blotting and co-immunoprecipitation. Results Upregulation of TBC1D2 was found in OC and was associated with a poor prognosis. Meanwhile, TBC1D2 promoted OC cell proliferation, migration, and invasion in vitro and facilitated tumor growth and metastasis in vivo. Moreover, TBC1D2 contributed to OC cell invasion by E-cadherin degradation via disassembling Rac1-IQGAP1 complex. In addition, miR-373-3p was screened out and identified to inhibit OVCAR3 invasion via negative regulation of TBC1D2. Conclusion Our findings indicated that TBC1D2 is overexpressed in OC and contributes to tumor metastasis via E-cadherin degradation. This study suggests that TBC1D2 may be an underlying therapeutic target for OC.